Tunable photochemical 6π heterocyclization reactions mediated by a boron Lewis acid. (1st October 2021) - Ma, Lishuang; Feng, Wenxu; Shang, Hongyan; Lin, Xufeng; Xi, Yanyan
Abstract : The regulation effect of boron Lewis acid catalyst on the photoinduced 6π heterocyclization was investigated by using multi-configurational ab initio calculations. Abstract : Lewis acid catalysts are of great interest for regulating the excitation energy, reactivity, and enantioselectivity of photochemical transformations. However, the understanding of their catalytic performance toward 6π photocyclization is still quite sparse. We provide here a mechanistic insight into the regulation effect of a boron Lewis acid (BF3 ) on the photochemical 6π heterocyclization of a β-enaminone investigated using multi-configurational ab initio calculations. Our state-of-the-art computational results reveal that the 6π heterocyclization of a free enaminone substrate tends to take place in the triplet 3 ππ* state, which relies on a 1 nπ* electronic excitation and an El-Sayed type singlet–triplet crossing. The excitation energies and properties of the enaminone can be photochemically tuned in the presence of a BF3 Lewis acid catalyst. As an important consequence, the catalyzed 6π heterocyclization can proceed smoothly on the singlet 1 ππ* hypersurface, and it may also occur in triplet manifold when choosing a suitable photosensitizer enabling the direct photochemical activation of the enaminone to the triplet excited state.